Fiction absolute and ethics: Tom Wolfe‘s back to blood - Jamshidian, Sahar; Pirnajmuddin, Hossein (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
Tom Wolf once more in his last novel Back to Blood (2012) has taken the issue of race and ethnic tensions as one of its primary themes and this time he has chosen the city of Miami, home to the highest proportion of foreign-born residents of any US major metropolitan area. This novel looks into the interethnic relationships among the Cuban immigrants, Haitians, and American whites and blacks. Applying Emmanuel Levinas’s theory of alterity and ethics of sensibility to Back to Blood could be rewarding since it sheds light on the interethnic tensions present among different groups of people whose only concern is their own ‘blood’ and their own race. We argue that Wolfe’s novel, read in terms of ethics of sensibility, with its emphasis on the responsibility of one for the naked, universal Other, reveals how altericide and indifference towards the plight of the Other lie at the heart of most interethnic tensions and conflicts.